Parental attitudes and screen media utilization among preschool children in selected barangay day care centers in Diliman, Quezon City - Decena, Ma. Clarissa Isabel F.; Nonong, Alpha Mae S.; De Leon, Maria Perlita E. (Quezon City College of Home Econommics, University of the Philippines Diliman, 2013)
ABSTRACT Children today are living in a media saturated environment. The utilization of numerous types of screen media has become a regular part of young children's daily routines. Parents have been seen to have a strong influence on their children's screen media utilization as they model screen media consumption behavior and impose control over their children's media consumption. This study seeks to investigate the age and sex differences in 3- to 5-year-old children's screen media utilization and the relationship between parental attitude and the child's screen media utilization. Television, computer and android phone are the only screen media platforms considered in this study. A total of 89 parents (X = 34.54) of 3- to 5-year-old children enrolled in barangay day care centers were surveyed to gather data on their attitude towards screen media and their children's screen media utilization. Twenty-three of the 89 parents were then interviewed to gain more insight on their attitude towards screen media, their media parenting styles and their children's screen media utilization. The results of the study revealed that there is no significant difference between the screen media utilization of male and female children. Moreover, there are no significant differences between the screen media utilization of 3-year-old, 4-year-old and 5-year-old children. It has also been found out that there is a relationship between parental attitudes and the child's computer and android phone utilization. Indeed, parental attitudes influence their children's screen media utilization. Although, other factors like parent's education, parent's age have been seen to affect the children's utilization of different screen media platforms.
Thesis (BSFLCD)--University of the Philippines Diliman.
Keywords: Children and mass media -- Philippines